2017
DOI: 10.1111/jocd.12402
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum markers for postacne scarring

Abstract: Serum levels of hepcidin and CRP are promising markers, which may be considered as objective tools to predict the possibility of postacne scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…There were no statistically significant differences between the patient groups and control healthy group regarding gender and age and marital status between the studied groups (matched groups). This came in agreement with El-Taweel et al [22] who found that There were 44 (73.3%) female and 16 male (26.7%) patients. Female predominance may be due to hormonal changes during menstruation or higher level of stress among females [18] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were no statistically significant differences between the patient groups and control healthy group regarding gender and age and marital status between the studied groups (matched groups). This came in agreement with El-Taweel et al [22] who found that There were 44 (73.3%) female and 16 male (26.7%) patients. Female predominance may be due to hormonal changes during menstruation or higher level of stress among females [18] .…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that the range of patients age with acne lesions was 14.0 to 33.0 years with a mean of (23.5±5.77), in patients with post acne scars was15.0 to 35.0 years with a mean of (24.63±5.05) and in control group was 15.0 to 35.0 years with a mean of (25.80±5.81).The mean age in our study was in agreement with El-Taweel et al [22] who found that the mean age of the acne patients was( 19.57 ± 2.81 years).…”
Section: Discussionsupporting
confidence: 91%
“…It was thought that scars mainly follow nodulocystic acne lesions, but it has been shown that even noninflammatory acne lesions and mild degrees of acne can cause disfiguring postacne scarring 33 . That's why it would be of great benefit to find out more reliable laboratory markers 34 or genetic factors which would help in expecting patients susceptible to postacne scarring formation more accurately. The small sample size and not correlating different genotypes with the tissue expression of MMP‐1 and TIMP‐1 are the main study limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that scars mainly follow nodulocystic acne lesions, but it has been shown that even noninflammatory acne lesions and mild degrees of acne can cause disfiguring postacne scarring. 33 That's why it would be of great benefit to find out more reliable laboratory markers 34…”
Section: F I G U R E 3 Timp-1 (372 C/t) Alleles and Genotypes In Male...mentioning
confidence: 99%
“…C sensitive protein (CRP) may be proportionally correlates of the seriousness for incendiary skin inflammation vulgaris. Its vicinity over av might help those group defenses against p. Acnes and also to tissue harm through its Different movements of the included resistant phones and incendiary mediators [18]. Serum follistatin focuses in people gives the idea should parallel serum ctouchy protein levels [19].…”
Section: Discussionmentioning
confidence: 99%